EPR, UV-Visible, and Near-Infrared Spectroscopic Characterization of Dolomite - S. Lakshmi Reddy; R. L. Frost; G. Sowjanya; N. C. G. Reddy; G. Siva Reddy; B. J. Reddy (Advances in Condensed Matter Physics)
Dolomite mineral samples having white and light green colors of Indian origin have been characterized by EPR, optical, and NIR spectroscopy. The optical spectrum exhibits a number of electronic bands due to presence of Fe(III) ions in the mineral. From EPR studies, the parameters of g for Fe(III) and g,A, and D for Mn(II) are evaluated and the data confirm that the ions are in distorted octahedron. Optical absorption studies reveal that Fe(III) is in distorted octahedron. The bands in NIR spectra are due to the overtones and combinations of water molecules. Thus EPR and optical absorption spectral studies have proven useful for the study of the solid state chemistry of dolomite.